Natural abiotic iron-mediated formation of C1 and C2 compounds from environmentally important methyl-substituted substrates and their implication for nature (digital appendix) - Hädeler, Jonas (Universität, 2025)
Organic and inorganic compounds with one or two carbon atoms (C1 and C2) are continuously produced through natural processes, including methane, ethane, methanol, formaldehyde, methyl chloride, and carbon dioxide. These compounds act as greenhouse gases, control the oxidation capacity of the atmosphere, and play an important role in atmospheric chemistry and physics. A recent study has provided compelling evidence for the oxic and abiotic formation of C1 and C2 compounds through the cleavage of methyl groups from environmentally relevant organic substrates with sulfur-, nitrogen-, phosphorus-, and oxygen-bonded methyl groups using iron-oxo species. The results show that these processes are a significant source of C1 and C2 compounds, influencing the global carbon cycle. In particular, the demethoxylation of lignin monomers and other aromatic methoxy compounds is an important process occurring in natural environments such as soil. This discovery highlights the importance of abiotic processes for the production of C1 and C2 compounds and their impact on the chemical and physical properties of natural environments.